EFEKTIVITAS INSENTIF PAJAK DAN KEBIJAKAN DI BIDANG PERPAJAKAN SEHUBUNGAN DENGAN PANDEMI COVID-19 - Suwandi, Eko Darmawan (Finance and Banking Program, Accounting Department, Politeknik Negeri Semarang, 2022)
This research aims to analyze the effectiveness of tax incentives and policies in the field of taxation in connection with the Covid-19 pandemic. The research findings show that the impact of the government's tax policy has not been said to be effective but has shown a positive impact in the form of an increase in revenue from domestic tax components in 2021 compared to 2020, namely Income Tax increased by 2.0%, Value Added Tax and Sales Tax on Goods. Luxury rose 2.2%, Land and Building Tax increased 10.3%, Excise increased 4.5%, and Other Taxes increased 66.1%. The impact of taxation policies can also be seen from the increase in revenue from the international trade tax component in 2021 compared to 2020, namely state revenues from import duties which increased by 4.2% and export taxes increased by 8.1%.